Strategi Motivasi bagi Wali Santri Tahfidz di Pondok Pesantren Nurul Qur’an - Siti Basiroh; Abdussyukur Abdussyukur (ANWARUL, 2025)
This study addresses the overlooked area of motivational tactics employed by parents of Qur’an memorization students (wali santri), despite their critical role in supporting perseverance and memorization success. The research aims to explore the motivational strategies used by parents through the application of Keller’s ARCS Model (Attention, Relevance, Confidence, Satisfaction) and to explain the influence of Islamic values on the development of sustainable spiritual motivation. Using a qualitative phenomenological approach, the study involved nine key informants—including pesantren caretakers, tahfidz instructors, and parents—selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the four ARCS components assimilate with Qur’anic principles such as sincere intention (niat), reliance on God (tawakkal), consistency (istiqamah), and acceptance (ridha), resulting in motivation that is both psychological and spiritual. The emerging concept of transformational-spiritual motivation combines psychological approaches with religious consciousness, offering new insights into the context of tahfidz education. Theoretically, this study extends the ARCS Model by integrating an affective-transcendental system, while practically, it emphasizes the importance of Qur’an-based mentoring programs to strengthen religious motivation and moral cohesion within tahfidz families.